Chemical Synthesis and Enzymatic Modification of Mangostins: A Comprehensive Review on Structural Modifications for Drug Discovery - Lew, Jordan Joon-Yip; Choo, Yeun-Mun (Current Medicinal Chemistry, 2025)
Mangostins, a prominent component of Garcinia mangostana, have been extensively studied for their biological activities and structural modifications. Chemical methods, including cyclization reactions under acidic conditions, have yielded many derivatives, which often exhibit enhanced pharmacological properties compared to itself. Enzymatic biotransformation, such as glycosylation and oxidation mediated by fungal species and enzymes like horseradish peroxidase, have provided regioselective pathways to functionalized mangostin derivatives. These studies highlight the versatility of mangostin as a scaffold for designing compounds with tailored biological functions. Overall, mangostin represent a promising platform for developing compounds with enhanced pharmacological activities, paving the way for innovative approaches in biomedicine and pharmaceutical sciences. This review provides a comprehensive examination of the chemistry of mangostins, detailing their total synthesis and the derivatives obtained through both chemical and enzymatic methodologies.
Keywords: 9-hydroxycalabaxanthone